2013
DOI: 10.1007/s12262-013-0857-9
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Cholecystectomy Without Prophylactic Antibiotics: A Prospective Study

Abstract: Laparoscopic cholecystectomy has become the new gold standard for management of symptomatic gallstones. Prophylactic antibiotics are used in elective surgery by the majority of surgeons, and their role in biliary tract surgery has been well established for a subpopulation of high-risk patients. This consensus has been derived from multiple studies involving biliary tract surgery before and in the era of laparoscopic cholecystectomy. But the use of prophylactic antibiotics in laparoscopic cholecystectomy especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
1
4
0
1
Order By: Relevance
“…6 Many studies revealed that women of age group above 20 years are most likely affected with cholecystitis. 3,5 This was in accordance with the present study findings. About 14 females of age group between 21-30years were affected in this study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…6 Many studies revealed that women of age group above 20 years are most likely affected with cholecystitis. 3,5 This was in accordance with the present study findings. About 14 females of age group between 21-30years were affected in this study.…”
Section: Discussionsupporting
confidence: 93%
“…Open cholecystectomy is the most important technique, but laparoscopic cholecystectomy is now the gold standards due to its advantages like less invasive and less tissue involvement. 5 Prophylactic use of antibiotics is an important component of biliary tract surgery, and there is about 50% decrease in the incidence of postoperative wound infection with the use of preoperative antibiotics. 6 Many studies revealed that women of age group above 20 years are most likely affected with cholecystitis.…”
Section: Discussionmentioning
confidence: 99%
“…9 High-risk LC patients are identified as follows: patients over 60 years of age; those with a history of diabetes, immunosuppression, biliary stones and obstruction, cholangitis, or jaundice; patients with a history of colic within 30 days before surgery; patients with cholecystitis at the time of surgery; and patients with a history of previous biliary surgery. 18 A study conducted on 277 patients undergoing LC 19 and another study that examined 1037 patient 6 reported that there was no statistically significant effect of prophylactic antibiotic use prior to low-risk LC on the development of postoperative infection. All of these meta-analyses reported that there was no difference between the prophylactic group and the non-prophylactic group in terms of infection and that it was therefore not necessary to apply prophylaxis before low-risk LC.…”
Section: Discussionmentioning
confidence: 99%
“…1,[13][14][15][16][17] In another study where LC was performed on 102 patients and prophylactic antibiotics were not applied, it was concluded that prophylactic antibiotic use before low-risk LC was not necessary. 18 A study conducted on 277 patients undergoing LC 19 and another study that examined 1037 patient 6 reported that there was no statistically significant effect of prophylactic antibiotic use prior to low-risk LC on the development of postoperative infection. In a study of 429 patients who underwent low-risk LC, the rate of infection was 1.7% and 2.1% in 182 patients with prophylaxis and 247 patients without prophylaxis, respectively; however, no statistically significant difference was found.…”
Section: Discussionmentioning
confidence: 99%
“…O controle glicêmico perioperatório reduz o risco de ISC, mortalidade e tempo de internação hospitalar(FREITAS et al, 2013). durante o ato cirúrgico, foi considerada como fator de risco para o aumento das chances de desenvolvimento de ISC em cirurgias de colecistectomia videolaparoscópica, e os dados foram pautados em relatos de série de casos de abscessos contendo cálculos biliares em seu interior(HORTON; FLORENCE, 1998) FREIER, ALBEAR, 1999;CHONG et al, 2015;MANDAL et al, 2015;PASQUALI et al 2016)…”
unclassified